Testing (modified) gravity with 3D and tomographic cosmic shear - Spurio Mancini, Alessio; Reischke, Robert; Schäfer, Björn Malte; Pettorino, Valeria (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. Cosmic shear is one of the primary probes to test gravity with current and future surveys. There are two main techniques to analyse a cosmic shear su